2013
DOI: 10.1021/ie402853g
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Mo(VI) Selective Separation by Eriocheir sinesis Crab Shells Gel

Abstract: In the present study, crab shell chitin (CSC) has been used for the recovery of Mo(VI) from Cu/Fe containing solutions. The CSC gel showed a high affinity for Mo(VI) compared with other adsorbents, and the maximum adsorption capacity was evaluated as 252.27 mg g −1 in the case of pH 1, which could be explained by the structure of the CSC gel, containing more reactive −OH and/or −NH groups binding Mo(VI) ions. The experimental results fit satisfactorily to the Langmuir isotherm in comparison to the Freundlich, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Thus, it is essential to develop appropriate technologies for separating and recovering divalent cadmium (Cd(II)) ion from wastewater. Currently, several conventional approaches including chemical precipitation, solvent extraction and membrane filtration have been applied for the sequestration of heavy metals (Jacques et al, 2007;Xiong et al, 2014). However, these methods suffer from drawbacks, such as a high operating cost, incomplete removal or voluminous sludge generation, and may not be suitable for small-scale industries.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is essential to develop appropriate technologies for separating and recovering divalent cadmium (Cd(II)) ion from wastewater. Currently, several conventional approaches including chemical precipitation, solvent extraction and membrane filtration have been applied for the sequestration of heavy metals (Jacques et al, 2007;Xiong et al, 2014). However, these methods suffer from drawbacks, such as a high operating cost, incomplete removal or voluminous sludge generation, and may not be suitable for small-scale industries.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, Langmuir, Freundlich, Temkin and Dubinin-Radushkevich equations, which were expressed in our previous work (Xiong et al 2014), have been used to fit the experimental data through non-linear regression techniques to check for their adequacy to represent the experimental data. The adsorption isotherms studies for Mo(VI) on the amine-functionalized mesoporous silica were carried out with different concentrations of individual metal solutions at pH 1, and the adsorption isotherm constants have been depicted in Table S1 in supplementary information.…”
Section: Adsorption Isotherms Of Mo(vi) On the Aminefunctionalized Mementioning
confidence: 99%
“…[13][14][15][16][17] Therefore, many different methods, such as solvent extraction, ion exchange, and adsorption, have been developed to recover Mo(VI) from various aqueous media. [18][19][20][21][22][23][24] Among them, the adsorption method is widely preferred due to its simplicity of operation, low investment, easy regeneration, and effectiveness in dealing with various pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum load capacity of the crosslinking persimmon tannin is only 53.73 mg•g −1 . 25 Some researchers have reported that ligands containing N donor atoms interact strongly with the Mo(VI) anionic complexes due to protonated amines interacting with Mo(VI) in acidic solutions 10,20,[26][27][28][29] A series of nitrogen-containing functional groups modified persimmon tannin adsorbents, including amine-modified persimmon tannin (172 mg•g −1 ), diethylamine modified persimmon tannin (216.3 mg•g −1 ), and triethylamine modified persimmon tannin (235.2 mg•g −1 ), were prepared to enhance the recovery capacity and selectivity of Mo(VI). 30,31 However, the maximum adsorption capacity of these modified persimmon tannin adsorbents is not ideal due to the small nitrogen-containing functional groups and the large steric hindrance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation